Influence of monsoon seasons on accidental chlorine leak and dispersion around Gebeng industrial area - Law, Woon Phui; Badhrulhisham, Abdul Aziz; S. I., Rani; Jolius, Gimbun (IOP Publishing, 2020)
This paper presents the prediction of hypothetical chlorine leak dispersion around Gebeng industrial area using Areal Location of Hazardous Atmosphere (ALOHA) software. The effect of the different wind speed and direction to chlorine dispersion in the meteorological microscale area was investigated. The wind speed ranging from 1.32 to 10.7 m/s obtained from a local weather station was considered. Heavy gas dispersion model was used to determine the concentration of chlorine plume within the area of concern. The leakage rate was set to correspond to a leakage from the chlorine tank at 792 kg/h. The result showed that the residential areas R1 and R2 are affected by the plume dispersed by southwest and northern winds, respectively. A greater hazard area was found when the wind speed is below 2.3 m/s. Meanwhile, the hazard zone reduced to nearly half when the wind speed is above 5.4 m/s. The appropriate evacuation routes were developed to reduce risk of exposure to toxic gas. Finding from this work is useful to understand the risk of noxious gas dispersion around Gebeng industrial area.